The Intraday Relation between Return Volatility, Transactions and Volume - WU, Chunchi (Institutional Knowledge at Singapore Management University, 1999)
In this article, we examine the relation between return volatility, average trade size, and the frequency of transactions using transaction data. Consistent with Jones, Kaul, and Lipson (1994)(. Review of Financial Studies, 7, 631–651), our results show that the frequency of trades has a high explanatory power for return volatility. However, contrary to their finding, we find that average trade size contains nontrivial information for return volatility. The positive relation between return volatility and average trade size is more significant for actively traded stocks. Furthermore, return volatility exhibits significant intraday variations. It is found that the effect of trade frequency on return volatility is much stronger in the opening trading period.